A first-principles study of Mg/Ni induced magnetic properties of Zn0.95-xMgxNi0.05O - (:unkn) unknown (ELSEVIER, 2020)
Magnetic properties of Mg/Ni doped ZnO were investigated by the first-principles study. The generalized gradient approximation (GGA) in Perdew-Burke-Ernzerhov of the scheme as a form of density functional theory (DFT) utilizing the plane-wave pseudo-potential method was used. Calculations were performed for a constant Ni doping ratio as 5% and different concentrations of Mg varying from 1% to 5%. It was shown that Mg concentrations helped to tune band gap and mediate the ferromagnetic property. 1% Mg-doped structure had a half-metallic ferromagnetic (HMF) state. Meanwhile, metallic behavior (MB) was observed for higher concentrations of Mg ( > 1%) impurities. It was revealed that Mg-doped ZnNiO possesses ferromagnetic behavior solely for 1% Mg while other doping ratios were showing distinctive phases including antiferromagnetism (AFM). Besides, there is no evidence of a clear connection between the doping concentration of the Mg and the magnetic phase. Ni distant/near oxygen vacancies (V-0) enhanced the FM state; however, distant vacancies led to HMF state for all Mg concentrations. Zn-d, O-p, and Ni-d (dominates) control the spin-up/down channels by hybridization.
Keywords: Mg/Ni doped ZnO; First-principles; Nanostructures; Ab-initio calculations; Electronic property; Magnetic property; Density functional theory; Perdew-Burke-Ernzerhof; Generalized gradient approximation; NI-DOPED ZNO; ROOM-TEMPERATURE FERROMAGNETISM; HYDROTHERMAL SYNTHESIS; FILMS; OXIDE